Implementasi Model Reasoning and Problem Solving Berbantuan Lingkungan Sekitar dalam Pembelajaran IPA di Madrasah Ibtidaiyah - salamah, umi (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2019)
Natural Science (IPA) is the process of learning and understanding the universe through observation so that a concept is obtained. The concept can be varied, according to the experience and information obtained. Based on preliminary observations on fourth-grade students of MI Al-Hidayah it is known that mastery of the science concept is still low, this can be seen from the pre-test results of only 8 students who completed/met the KKM of 30 students. This study aims to determine the implementation of science learning with reasoning and problem-solving models assisted by the surrounding environment in science learning and to determine the understanding of science concepts after applied reasoning and problem-solving models assisted by the surrounding environment. This type of research is classroom action research (CAR) which consists of two cycles, each cycle consisting of four stages, namely planning, action, observation, and reflection. The reasoning and problem-solving model is a learning model that has five stages, namely: 1) reading and thinking 2) exploring and planning, 3) selecting strategies, 4) finding answers, 5) reflecting. The subjects of this study were the fourth-grade students of MI Al-Hiadayah Wajak-Malang, amounting to 30 students. Data collection in this study uses observation techniques, unstructured interviews, documentation, and field notes. The instruments used were the RPP preparation observation sheet and the application of reasoning and problem-solving models, student activities, documentation, field notes, and written tests. The implementation of reasoning and problem-solving models of science subjects is able to improve the understanding of students' concepts about science, capable of fixing the misconceptions that occur in students so that it influences the improvement of student learning outcomes.